Teaching and learning of Autocad on Massive Open Online Course (MOOC) for town and regional planning programme, UiTM Perak Branch / Nor Hisham Md Saman ... [et al.] - Md Saman, Nor Hisham; Sanusi, Mohamad Sofiyuddin; Mat Zin, Mohd Roswodi; Haron, Norhazlan; Ismail, Izzamir (2020)
The Industrial Revolution 4.0 and the COVID-19 global pandemic have impacted face-to-face traditional teaching and learning. They demand the teaching environment to be responsive and proactive. The Massive Open Online Course (MOOC) is seen to be a viable alternative approach in teaching and learning. Its ability to function remotely in graphical, active, and interactive ways is viewed as its main forte. The Computer-Aided Design (AutoCAD) course, on the other hand, relies heavily on its orthodoxy way of teaching and learning drafting software application such as Autodesk that involve hands-on and demonstration. Acknowledging this incongruence and by applying MOOC for the AutoCAD course attempt to remedy the current approach by mixing and combining three delivering and learning activities: i) PowerPoint; ii) Video, and iii) Google Meet. The contribution of these in MOOC for AutoCAD is significant as it could provide a framework for other technical and computer courses that utilise online teaching.